2022
DOI: 10.1021/acsami.1c22974
|View full text |Cite
|
Sign up to set email alerts
|

Bilayer Nanoporous Polyethylene Membrane with Anisotropic Wettability for Rapid Water Transportation/Evaporation and Radiative Cooling

Abstract: Both sweat drainage and evaporation play important roles in achieving personal moisture and thermal management during sweat-producing exercises. However, it remains a great challenge to simultaneously realize thermal management through radiative cooling for human body without perspiration. Herein, we report a bilayer nanoporous polyethylene membrane with anisotropic wettability, which possesses superior radiative cooling ability (∼2.6 °C lower than that of cotton) without perspiration. Meanwhile, it realizes e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 41 publications
0
34
0
Order By: Relevance
“…The optical properties of PMMA are discussed in this section before and after pore-forming. The extinction coefficient ( k ) is an important parameter that reflects the emission performance of the material in the infrared spectral band. , The reflection index ( n ) and extinction coefficient ( k ) are both shown in Figure a,b, respectively, based on refs and. It was shown that the multiple extinction peaks of PMMA were found in the transparent window band of the atmosphere.…”
Section: Resultsmentioning
confidence: 99%
“…The optical properties of PMMA are discussed in this section before and after pore-forming. The extinction coefficient ( k ) is an important parameter that reflects the emission performance of the material in the infrared spectral band. , The reflection index ( n ) and extinction coefficient ( k ) are both shown in Figure a,b, respectively, based on refs and. It was shown that the multiple extinction peaks of PMMA were found in the transparent window band of the atmosphere.…”
Section: Resultsmentioning
confidence: 99%
“… 59 And Zhao's group reported a porous polyethylene membrane with anisotropic wettability, which could possess superior radiative cooling ability without perspiration. 102 …”
Section: Application Of a Monolayered Porous Membranementioning
confidence: 99%
“…Perspiration evaporation plays an indispensable role in human wet regulation. Avoiding increased sweat or moisture on the skin becomes the focus of wet management . Traditional textiles, such as cotton and silk fabric, show excellent water adsorption capacity resulting from their wicking behavior and drain out sweat or moisture from the human skin effectively, alleviating the sense of wettedness quickly .…”
Section: Introductionmentioning
confidence: 99%
“…Avoiding increased sweat or moisture on the skin becomes the focus of wet management. 1 Traditional textiles, such as cotton 2 and silk fabric, 3−5 show excellent water adsorption capacity resulting from their wicking behavior and drain out sweat or moisture from the human skin effectively, alleviating the sense of wettedness quickly. 6 However, such a wicking behavior shows the so-called bidirectional property, that is, sweat or moisture can be transported from the human skin to the environment as well as in the reverse direction.…”
Section: ■ Introductionmentioning
confidence: 99%